Atrial fibrillation is highly prevalent yet undertreated in patients with biopsy‐proven nonalcoholic steatohepatitis. (21st December 2018) - Whitsett, Maureen; Wilcox, Jane; Yang, Amy; Zhao, Lihui; Rinella, Mary; VanWagner, Lisa B.
Abstract: Background & Aims: Nonalcoholic steatohepatitis (NASH) is associated with increased cardiovascular disease. Atrial fibrillation is a prominent risk marker for underlying cardiovascular disease with a prevalence of 2% in patients <65 years old. Atrial fibrillation prevalence in NASH is unknown. We sought to assess the prevalence and impact of atrial fibrillation on healthcare utilization in NASH. Methods: Patients were identified from a tertiary care centre Electronic Database from 2002 to 2015. International Classification of Diseases 9 (ICD9) codes identified comorbidities and atrial fibrillation. Descriptive statistics were used to compare characteristics between patients with NASH with and without atrial fibrillation. Results: Of 9108 patients with ICD9 diagnosis of NASH, 215 (2.3%, mean age 57 years, 32% male) had biopsy‐proven NASH. Atrial fibrillation prevalence was 4.6%. Patients with NASH and atrial fibrillation had a higher prevalence of heart failure (54.5% vs 8.8%, P  < 0.001) and cerebrovascular (27.3% vs 2.0%, P  < 0.001) or vascular disease (54.5% vs 13.2%, P  = 0.002), compared to NASH without atrial fibrillation. All patients with NASH and atrial fibrillation had a CHA2DS2VASc score ≥2 indicating high stroke risk and need for anticoagulation. Eight of 10 patients were eligible for anticoagulation and 5 of 8 (62.5%) received appropriate therapy. Conclusion: Atrial fibrillation prevalence is two‐fold higher in patients with NASH compared to the general population. Patients with NASH have a high risk of stroke; however, many do not receive appropriate guideline‐directed therapy. Future studies are needed to identify whether guideline‐based management of atrial fibrillation in NASH reduces cardiovascular morbidity and mortality. Abstract : See Editorial on Page818